Flexible Pavement Design Analysis Using Bina Marga 2017 Method for the Road Section from Banjang-Pulau Nyiur to Batu Mandi, Hulu Sungai Utara - Rezky Anisari; Ria Adriyati; Abdul Hafizh Ihsani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Banjang, Pulau Nyiur, Batu Mandi road is one of the provincial roads in South Kalimantan located in the Hulu Sungai Utara. This road falls under the jurisdiction of the South Kalimantan Provincial Government and has a total length of 12.5 km. Some parts of this road still lack asphalt pavement, and there are plans for future improvements to enhance driving comfort and facilitate inter-regional transportation. Therefore, there is a need for appropriate pavement thickness planning that aligns with the field conditions and regulations. This study employs the flexible pavement thickness planning method according to the Bina Marga 2017 guidelines, with a design life of 20 years and a traffic growth rate of 3.5%. The surface thickness planning utilizes Asphalt Concrete (AC) with a wearing course (AC WC), and an AC Base layer with LPA Class A aggregate gradation. The results of this study indicate that the calculated flexible pavement thickness using the Bina Marga 2017 method is 58 cm, comprising a 10 cm AC WC layer, an 18 cm AC Base layer, and a 30 cm LPA Class A aggregate layer